The golden goblet - McGraw, Eloise Jarvis (New York Scholastic Books, 1992)
A young Egyptian boy struggles to reveal a hideous crime and reshape his own destiny.
Keywords: Detective and mystery stories; Egypt -- History -- To 332 B.C. -- Juvenile fiction